Tissue-specific expression of distinct spectrin and ankyrin transcripts in erythroid and nonerythroid cells (The Rockefeller University Press, 1985)
cDNA probes for three components of the erythroid membrane skeleton, alpha spectrin, beta spectrin, and ankyrin, were obtained by using monospecific antibodies to screen a lambda gt11 expression vector library containing cDNA prepared from chicken erythroid poly(A)+ RNA. Each cDNA appears to hybridize to one gene type in the chicken genome. Qualitatively distinct RNA species in myogenic and erythroid cells are detected for beta spectrin and ankyrin, while alpha spectrin exists as a single species of transcript in all tissues examined. This tissue- specific expression of RNAs is regulated quantitatively during myogenesis in vitro, since all three accumulate only upon myoblast fusion. Furthermore, RNAs for two of the three genes do not accumulate to detectable levels in chicken embryo fibroblasts, demonstrating that their accumulation can be noncoordinate. These observations suggest that independent gene regulation and tissue-specific production of heterogeneous transcripts from the beta spectrin and ankyrin genes underlie the formation of distinct membrane skeletons in erythroid and muscle cells.